2022
DOI: 10.3390/v14102300
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bacillus-Infecting Bacteriophage B13—The Founding Member of the Proposed New Genus Bunatrivirus

Abstract: In this work, we describe a novel temperate bacteriophage, Bacillus phage B13. Bacillus-infecting phages are widespread and abundant, though often overlooked including because of their temperate lifestyle. B13 was isolated from its bacterial host via mitomycin C induction. Its host range was determined, and its pH and thermal stability were evaluated. The whole genome of B13 was sequenced and annotated. The genome is 36,864 bp long and contains 53 genes. The tail genes of B13 suggest that the phage has a sipho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…Similar results were obtained in the study conducted by Kozantsev et al [ 73 ], where the growth kinetics of Bacillus cereus strain VKM B-370 after infection with the lysogenic phage B13 at different MOIs was determined. It was shown that the higher the MOI, the faster the partial growth inhibition was achieved.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Similar results were obtained in the study conducted by Kozantsev et al [ 73 ], where the growth kinetics of Bacillus cereus strain VKM B-370 after infection with the lysogenic phage B13 at different MOIs was determined. It was shown that the higher the MOI, the faster the partial growth inhibition was achieved.…”
Section: Resultssupporting
confidence: 89%
“…The lower values of the specific growth-rate coefficient (µ) determined for the phage-infected cultures indicate the significant inhibition of cell divisions in the log phase. Similar results were obtained in the study conducted by Kozantsev et al [73], where the growth kinetics of Bacillus cereus strain VKM B-370 after infection with the lysogenic phage B13 at different MOIs was determined. It was shown that the higher the MOI, the faster the partial growth inhibition was achieved.…”
Section: Evaluation Of the Activity Of Phage Against Bacterial Hostssupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly to the Thurquoise, phage SIOphi – a herellevirus infecting B. subtilis , is inactivated in 60°C though the process is markedly slower ( Krasowska et al, 2015 ). Also a B. cereus BaceCM02 phage (that is unclassified but resembles Thurquoise morphologically) is sensitive to 50°C ( Phongtang and Chukeatirote, 2021 ; Kazantseva et al, 2022 ). Only ( Lee et al, 2014 ) claim that phages BPS10C, and BPS13 that are related to Thurquoise at the subfamily level, are stable at 50°C but fail to present raw data supporting this assertion.…”
Section: Resultsmentioning
confidence: 99%